PENGARUH KODE ETIK, PENGALAMAN KERJA DAN SITUASI AUDIT TERHADAP SKEPTISISME PROFESIONAL AUDITOR - Sagala, Ira Mahdayani; Sudarmadi (Jurnal Nusa Akuntansi, 2024)
This research aims to determine the influence of the Code of Ethics, Work Experience, and Audit Situation on the Skepticism of Professional Auditors at Public Accounting Firms in Tangerang. The population in this study were all auditors who worked at the Public Accounting Firm (KAP) in Tangerang with a sample size of 33 respondents. The sampling method used was the convenience sampling method. The data source used is primary data and the data collection method used is through a questionnaire distributed to auditors working in KAP in the Tangerang area. The analysis technique used is multiple linear regression analysis. Hypothesis testing uses the coefficient of determination test, F test, and T test. Data analysis uses SPSS version 29 software. The results of this study show that the code of ethics, work experience, and audit situation influence the professional skepticism of auditors.